O20 On-line STI testing services: improving access, efficiency and user experience. (18th May 2015) - Brady, Michael; Howroyd, Chris; Parry, Glyn; Baraitser, Paula; Holdsworth, Gillian; Menon-Johansson, Anatole
Abstract : Background/introduction: There are many barriers to accessing sexual health and HIV testing services. Novel service models could address this. On-line testing may provide a solution. Aim(s)/objectives: To evaluate the acceptability and potential impact of on-line STI testing. Methods: We developed a dedicated, secure website for free on-line STI testing. Website content and testing process was iteratively designed in response to user feedback. Simple questions identify those most at risk or symptomatic and signpost to local services. Clients order self-taken NAAT tests for chlamydia (CT) and gonorrhoea (GC) and a pin-prick blood test for syphilis and 4 th generation HIV testing and post them to the laboratory. Results are received by text. In November 2014 we piloted the process by offering it to clients attending 2 sexual health services. Results: 47 clients used the service. 31 (65.9%) men, of whom 5 (16%) were MSM. Mean age was 29 (range 19–64). Mean time to receipt of results was 3 days (range 0–8). 18 (38.3%) clients received their results on the same day the sample was taken. One client tested positive for syphilis. All other tests were negative. User feedback was predominantly positive, with specific reference to its speed and simplicity. 8/47 (17%) left negative feedback about the pinprick process, which they found difficult or unpleasant. Discussion/conclusion: The service was highly acceptable. Rapid results turnaround was more efficient than local 'traditional' services. The service (which soon becomes available to all local residents) will contribute significantly to local STI/HIV testing and prevention strategies.